THEORETICAL FOUNDATIONS OF THE CONCEPT OF LACUNA IN LINGUOCULTURAL AND TRANSLATION STUDIES (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The article discusses the concept of lacuna, its classification, its manifestations in intercultural communication, and its role in translation studies. It also emphasizes the issue of achieving balance in translation with the example of English-Uzbek and Uzbek-English comparisons. Approaching the term “lacuna” from the linguocultural point of view is highly supportedin the article. It is proved that the study of lacuna in the linguocultural aspect has a number of advantages. This approach can help to understand the lacuna in integrity, in all its beauty, to see deeper foundations of the lacuna, and to open up new perspectives and opportunities for understanding intercultural communication. In particular, we stand for the use of linguocultural analyses in Uzbek-English translation fiction, the languages, which are distant from each other, because in prose works there are many lexical units with a clear linguocultural component, and in most cases they are given the decisive roles as expressing the literary value and idea of the work. Deep background knowledge is required to properly understand and translate these lexical units. Insufficient understanding and incorrect translation can lead to misunderstandings and cultural errors in communication. In this context, this paper aims to show the benefits of a deeper and combined study of the lacuna in linguistic and cultural aspects. It is also stated in the article, that due to the complex and multifaceted nature of the lacuna, classifying them into a single principle becomes a very difficult task. It is only natural that a lacuna may be associated with a classification system based on a specific aspect of the lacuna, since one lacuna may belong to more than one classification system at a time. Contrary to a number of scholars, we emphasize the need for both lacuna studies to be conducted both synchronously and diagonally.